2016
DOI: 10.1093/sleep/zsw069
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Perception and Misperception in Chronic Cocaine Users During Abstinence

Abstract: Study Objectives: During abstinence, chronic cocaine users experience an objective worsening of sleep that is perceived as qualitatively improving. This phenomenon has been termed "occult insomnia." The objective of this study was to determine whether chronic cocaine users experience positive sleep state misperception during abstinence. Methods: Forty-three cocaine-dependent persons were admitted to an inpatient research facility for 12 days and 11 nights to participate in a treatment study of modafinil. Polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…This phenomenon was termed “occult insomnia” [24]. A follow-up study [56] showed that patients underestimated sleep onset latency, amount of time awake after sleep onset and overestimated total sleep time. Understanding of this phenomenon may provide insight to the underlying effects of cocaine (in this case) on sleep circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was termed “occult insomnia” [24]. A follow-up study [56] showed that patients underestimated sleep onset latency, amount of time awake after sleep onset and overestimated total sleep time. Understanding of this phenomenon may provide insight to the underlying effects of cocaine (in this case) on sleep circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, poorer self-reported sleep quality has been associated with more frequent use in CUD [5]. Furthermore, in the first weeks of abstinence, polysomnography (PSG) shows worsening sleep, with reductions in duration of rapid eye movement sleep (REM), slow-wave sleep (SWS), and total sleep, and increases in sleep latency [3,[6][7][8][9]. These sleep abnormalities are long-lasting [6] and related to the severity of withdrawal symptoms and clinical outcomes [10].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was termed "occult insomnia" [24]. A follow-up study showed that patients underestimated sleep onset latency, amount of time awake after sleep onset and overestimated total sleep time [56]. Understanding of this phenomenon may provide insight to the underlying effects of cocaine (in this case) on sleep circuitry.…”
Section: Subjective Measuresmentioning
confidence: 99%